Septic Embolic Stroke Followed by Hemorrhage and Brain Abscess in a Patient with Systemic Infections: A Case Report and Literature Review - Jama A. Mohamud; Jingtao Wu; Ye Jing; Yu Wang (Case Reports in Radiology)
We report a case of 50-year-old man with a severe acute ischemic stroke followed by intracerebral hemorrhage and brain abscess due to systemic infection. His initial intracranial radiographic findings were normal but three days later MRI scan of the brain revealed well-defined rounded cystic lesion on the T2-weighted and T1-weighted images in the right basal ganglia; the lesion presented an area of diffusion restriction on DWI; lately the lesion was confirmed to be an early stage of cerebral abscess. A week later the patient was noted to have worsening neurological status and left extremity weakness, and emergency brain CT scan revealed massive intracerebral hemorrhage in the right occipital lobe; he underwent intracranial hematoma evacuation surgery. The hematoma was removed successfully, and the systemic infections were treated with antibiotics.